A qualitative study to explore the attitudes of women and obstetricians towards caesarean delivery in rural Bangladesh - Begum, Tahmina; Sarker, Malabika (BMC pregnancy and childbirth, 2018)
Caesarean section is a lifesaving surgical intervention for women and their newborns, though overutilization is a public health concern. The caesarean rate in Bangladesh is approximately 23% overall, and in private facilities it is over 70%. It is essential to know both the supply side (obstetricians) and demand side (parturient women) views on caesarean birth in order to formulate specific interventions to address the escalating rate of caesareans.
Gesehen am 10.03.2020